The Importance Of Strategic Decision-Making By Enterprises In Sustainable Economic Growth - Khusanov Fakhriddin (Zien Journals, 2024)
Adhering to the organization's values allows you to see the future while setting goals, identifying threats, and making the best strategic decisions. No matter how trivial the problem may seem, the decision can affect the results of the organization. If such indicators occur in developed countries, the fact that this indicator is significantly higher in developing countries shows the relevance of our article. In this article, we will cover the extent to which the company's strategic decision-making affects the development of the company.
Keywords: Strategy; strategic decisions; strategic management; liquidity